2008
DOI: 10.1088/0954-3899/35/9/095007
|View full text |Cite
|
Sign up to set email alerts
|

Neutral scalar Higgs bosons in the USSM at the LHC

Abstract: We study the possibility of discovering neutral scalar Higgs bosons in the U (1) ′extended supersymmetric standard model (USSM) at the CERN Large Hadron Collider (LHC), by examining their productions via the exotic quark loop in the gluon fusion process at leading order. It is possible in some parameter region that the neutral scalar Higgs bosons may have stronger couplings with the exotic quarks than with top quark. In this case, the exotic quarks may contribute more actively than top quark in productions of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 66 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…The exotic quarks and squarks could appear in decays of the Z ′ , or may manifest themselves indirectly, since the production of the heaviest Higgs boson (via gluon fusion) can be dominantly mediated by loops of these exotics [452]. The production of neutral Higgs bosons in this class of models has been discussed in [478].…”
Section: U(1) ′ -Extensions Of the Nmssmmentioning
confidence: 99%
“…The exotic quarks and squarks could appear in decays of the Z ′ , or may manifest themselves indirectly, since the production of the heaviest Higgs boson (via gluon fusion) can be dominantly mediated by loops of these exotics [452]. The production of neutral Higgs bosons in this class of models has been discussed in [478].…”
Section: U(1) ′ -Extensions Of the Nmssmmentioning
confidence: 99%
“…[71,95]). There has also been a lot of work recently including investigations of the neutralino sector [96][97][98][99]; the relic density of dark matter [100]; GUT scale family symmetries which can explain the hierarchy of masses in the fermion sector and their associated mixings [101]; neutrino physics [102]; explanations of the matter-antimatter asymmetry of the Universe though EW baryogenesis or leptogenesis [93,94,103]; decays of the Z boson [104][105][106][107]; dipole moments [108]; anomaly mediated SUSY breaking with D-term contributions [109] and the (extended) Higgs sectors [110,111].…”
Section: U (1) Extensions and The E 6 Ssmmentioning
confidence: 99%
“…Now, we are ready for carrying out numerical analysis. The scheme for setting the relevant parameters is similar to our previous analysis [18][19][20][21][22]. First of all, we note that there are strong experimental constraints in the USSM on the mass of the extra gauge boson, m Z ′ , and on the size of the mixing angle |φ| between Z and Z ′ .…”
Section: Numerical Analysismentioning
confidence: 83%
“…The presence of these exotic quarks is interesting from the phenomenological point of view. In particular, scenarios with a light exotic quark in the USSM have extensively been investigated [18][19][20][21][22]. A recent study have shown that the exotic quarks may contribute by large amount to the CP mixing between the heaviest scalar and pseudoscalar Higgs bosons [18].…”
Section: Introductionmentioning
confidence: 99%